LEVEL OF USE OF LEMNA PERPUSILLA IN FEEDING ON SEED GROWTH CARP (CYPRINUS CARPIO) - Daniel Sinaga (Jurnal Perikanan Unram, 2024)
Feed production costs are the largest costs incurred by fish farmers. Carp (Cyprinus carpio) is quite popular among the public because of the delicious taste of its meat and its fairly affordable price. Caring for goldfish fry requires a lot of money if the feed used is 100% factory-made feed. It is necessary to look for additional feed whose protein content can reduce the use of commercial feed. The artificial feed needed is feed that has a high nutrient content, is easy to find in nature, and is widely available in nature. One of the feed raw materials derived from aquatic plants that can be used as additional feed is Lemna perpusilla. This type of aquatic plant can be used and has potential as an alternative source of protein for goldfish, namely the Lemna perpusilla aquatic plant. This research was carried out from June to July 2023 at UPR Amphibi Batang Toru. Completely Randomized Design (CRD) method: 5 (five) treatments and 3 (three) replications with a dose of 0% Lemna perpusilla as a control, followed by administration of 10%, 20%, 30% and 40% Lemna perpusilla. The final results of the research can be concluded that the addition of Lemna perpusilla is the most optimal and efficient in feed at 40% showing a significant effect on the growth of goldfish.